2021
DOI: 10.21031/epod.993571
|View full text |Cite
|
Sign up to set email alerts
|

Covariate Balance as a Quality Indicator for Propensity Score Analysis

Abstract: Propensity score analysis, such as propensity score matching and propensity score weighting, is becoming increasingly popular in educational research. When a propensity score analysis is conducted, examining the covariate balance is considered to be crucial to justify the quality of the analysis results. However, it has been pointed out that solely considering how covariates balance after matching may not be enough for justifying the quality of the propensity score analysis results. Suitable covariate balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Propensity score methods and traditional regression modelling, such as G-computation, tend to yield similar results [11], but this has yet to be investigated within our field of interest. Simulation studies have revealed that the variable selection has a bearing on the result when using propensity scores [12][13][14][15], but for unemployment and health this have not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Propensity score methods and traditional regression modelling, such as G-computation, tend to yield similar results [11], but this has yet to be investigated within our field of interest. Simulation studies have revealed that the variable selection has a bearing on the result when using propensity scores [12][13][14][15], but for unemployment and health this have not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%